(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
This descriptive-cum exploratory study was undertaken in the district hospital, Gurgaon in the State of Haryana to find out the status of maintenance and repair services for the major equipment in all areas of the hospital. The study was conducted by interviewing the concerned personnel using a structured questionnaire and by filling up a structured proforma for each item of major equipment. There was no system of regular maintenance either planned/scheduled or preventive. Only breakdown maintenance was found prevailing which was also neither proper nor convenient. The breakdown or out of order equipment was 36.5% of the total available equipment out of which only 20% was repairable and the rest 80% had become unserviceable lying for want of repairs for years. Based on the findings of the study and the discussions with concerned personnel and experts, suitable recommendations have been formulated.